(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As it is used in communication, internet communication tools began to use in education especially in English language learning. New trends technologies have supplemented English teaching in authencity and literacy such as reading, writing, speaking, and listening skills of students. English is the only valid language that can be understood by everyone all around the world. Students learn faster and easier than before because of the use of technology in schools. If they are trained during their school years, they have the chance of becoming experts in technology. It is proved by the researches that have been done early beginnings are always beneficial. Learning English through the web and using new trends in education in schools make students willing to learn the language. The aim of this study is to review technology in English learning activities and internet communication tools which are being used lately by instructors and learners. The study was conducted on the base of literature survey. Also, this study looks at Web-based English language learning tools, and tries to give information about internet communication tools also it is mentioned that how the teachers or instructors make educational environment more enjoyable. It is quite clear that English has become a necessity today. We need it in different fields of life. Web based technologies and powerful internet connections provide various new possibilities and latest trends for teachers and students.